Assessment of orthodontic treatment standard in Faculty of Dentistry, University of Malaya - Leong, B.L.; Zamzam, N.; Yassin, Z.Z.; Abdul, K.R. (2001)
The aim of this study is to evaluate the treatment outcome using fixed and removable appliances, in the Faculty of Dentistry, University of Malaya (U.M.). The study models of 25 fixed and 30 upper removable appliance cases, with complete written records were examined before and after orthodontic treatment using the PAR (Peer Assessment Rating) Index. All the data were analyzed using the Statistical Package for Social Sciences (SPSS) for Windows. Eighty five percent of the cases selected as sample were either 'improved' or 'greatly improved'. Among the 10 cases which were 'greatly improved', all had high pre-treatment PAR points (> 35 PAR points). Conversely, all the eight cases classified as 'worse or no different' were with low pretreatment PAR scores « 20 PAR points). The mean treatment duration in this study was 23. I months, ranging from 2 months to 78 months. The results of this study showed that the standard of treatment in this Faculty were fairly acceptable.